Relationship among oxidative DNA damage, gastric mucosal density and the relevance of cagA, vacA and iceA genotypes of Helicobacter pylori - Ladeira, Marcelo S. P. [UNESP]; Bueno, Roberta C. A. [UNESP]; Dos Santos, Bruna Fornazari [UNESP]; Pinto, Carla L. S. [UNESP]; Prado, Renato P. [UNESP]; Silveira, Marcela G. [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP]; Bartchewsky, Waldemar; Pedrazzoli, Jose; Ribeiro, Marcelo Lima; Salvadori, Daisy Maria Favero [UNESP] (Springer, 2008)
The aim of this study was to evaluate the relationship among oxidative DNA damage, density of Helicobacter pylori and the relevance of cagA, vacA and iceA genotypes of H. pylori. Gastric epithelial cells were isolated from 24 uninfected patients, 42 H. pylori infected patients with gastritis, and 61 patients with gastric cancer. Oxidative DNA damage was analyzed by the Comet assay, the density of H. pylori was measured by real-time polymerase chain reaction (PCR), and allelic variants of cagA, vacA and iceA were identified using the PCR. Infected patients by Helicobacter pylori cagA(+), vacAs1 m1 and iceA1 genotype showed higher levels of oxidative DNA damage than infected patients with H. pylori cagA(-), vacAs2 m2 and iceA2 genotypes and uninfected patients. Density of H. pylori did not influence oxidative DNA damage. Our results indicate that H. pylori genotype is more relevant than density for oxidative DNA damage.
Keywords: oxidative DNA damage; Helicobacter pylori; real-time PCR; Comet assay; gastric cancer; inflammation